(untitled) (The Thinker, 2024)
The focus of the conference is on anti-nuclear activism as part of the anti-apartheid struggle. We are curious to know of the international links during this period and the engagement with the government of the day. We are also curious to know the kind of actions that have been taken in the anti-apartheid struggle and engaging nuclear energy as part of that struggle.